2021
DOI: 10.3390/antiox10091455
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phytochemicals in Cancer Chemoprevention: Insights

Abstract: Cancer is a condition where the body cells multiply in an uncontrollable manner. Chemoprevention of cancer is a broad term that describes the involvement of external agents to slow down or suppress cancer growth. Synthetic and natural compounds are found useful in cancer chemoprevention. The occurrence of global cancer type varies, depending on many factors such as environmental, lifestyle, genetic etc. Cancer is often preventable in developed countries with advanced treatment modalities, whereas it is a painf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(112 citation statements)
references
References 206 publications
(188 reference statements)
0
112
0
Order By: Relevance
“…Accordingly, they have biological effects on diverse mechanisms, such as epigenetic modifications, modulation of signal transduction and metabolic pathways, and regulation of antioxidant enzyme activity [ 54 , 55 ]. In support of their advantageous effects, several data have been reported in literature, particularly regarding their anticancer activities [ 56 ] and their ability to delay or escape the onset and progression of CVD [ 57 ] or other chronic pathologies [ 58 ]. The phytochemicals with antioxidant-rich properties comprise the polyphenols, flavonoids, iso-flavonoids, anthocyanidins, phytoestrogens, terpenoids, carotenoids, limonoids, phytosterols, glucosinolates and fibres.…”
Section: From the Experimental Aspects To Translational Medicine: Ant...mentioning
confidence: 99%
“…Accordingly, they have biological effects on diverse mechanisms, such as epigenetic modifications, modulation of signal transduction and metabolic pathways, and regulation of antioxidant enzyme activity [ 54 , 55 ]. In support of their advantageous effects, several data have been reported in literature, particularly regarding their anticancer activities [ 56 ] and their ability to delay or escape the onset and progression of CVD [ 57 ] or other chronic pathologies [ 58 ]. The phytochemicals with antioxidant-rich properties comprise the polyphenols, flavonoids, iso-flavonoids, anthocyanidins, phytoestrogens, terpenoids, carotenoids, limonoids, phytosterols, glucosinolates and fibres.…”
Section: From the Experimental Aspects To Translational Medicine: Ant...mentioning
confidence: 99%
“…Active substances isolated from plants have been shown to exhibit different biological effects including anti-inflammatory, anti-malarial, antioxidant, antituberculotic, antibacterial, antifungal, antiviral, neuroprotective, antidiabetic, and many others [ 7 , 8 , 9 ]. Additionally, several lines of evidence indicated that various phytochemicals also possess antiproliferative and anticancer activity [ 10 , 11 , 12 ]. Chalcones, precursors in the synthesis of flavonoids and isoflavonoids in plants, have attracted attention due to their biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are known to stimulate biochemical reactions in cells [48]. Pharmacological activities such as anti-aging, antioxidant, anti-cancer, and anti-inflammatory effects have been reported for these plant bioactive compounds [49]. Therefore, this study was conducted to ascertain the anti-inflammatory activity and mechanisms of cryptochlorogenic acid isolated from A. adenophora, an invasive and toxic plant.…”
Section: Discussionmentioning
confidence: 99%